THE PESSIMISM IN POETRY AUGUSTO DOS ANJOS - Wellington Lima Amorim (Educação: Teoria e Prática, 2017)
Augusto dos Anjos is part of a select group of writers who, having dived deep into human existence, created in Brazilian literature works fleeing the commonplaces of his time and carnivalization condition attributed to the cultural diversity of Brazilian land, a view that is both distorted and obscured the true power of our artists. Pessimism takes thus an essential function: to question what you're doing and how you are doing, since all major pessimists are, deep down, great realistic. The purpose of this study is to evaluate the pessimism of Augustan poetry of the Angels and identify innovative reflections that his verses present. For this, read to your unique work, "I", and poems published in youth and some of his critics and leading scholars, as Raimundo Magalhaes Junior and poet Gullar. The methodology used was the literature review, assessing the poetry of the author and his work in identifying, compared to the thought of his time, the genesis of their uniqueness in our literature. Keywords: Poetry. Pessimism. Reflection.